2020
DOI: 10.1177/0844562120914424
|View full text |Cite
|
Sign up to set email alerts
|

Promoting First Relationships®: Implementing a Home Visiting Research Program in Two American Indian Communities

Abstract: Background Few, if any, home visiting programs for children under the age of three have been culturally adapted for American Indian reservation settings. We recently adapted one such program: Promoting First Relationships®. Objectives To culturally adapt Promoting First Relationships® while maintaining program fidelity, we used a community-based participatory approach to elicit input from two American Indian partners. Methods University-based researchers, reservation-based Native project staff, and Native trib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Few previous studies have explored the process itself in informal adaptation of paraprofessional support, and previous research has tended to focus on how informally adapted interventions are received [ 32 ] or how interventions can be systematically adapted through involvement of community members or stakeholders [ 30 , 33 , 35 ]. Our process differed from these mainly due to the fact that the ownership of the intervention, and thus its contextualization, resided with a different organization than the research project.…”
Section: Discussionmentioning
confidence: 99%
“…Few previous studies have explored the process itself in informal adaptation of paraprofessional support, and previous research has tended to focus on how informally adapted interventions are received [ 32 ] or how interventions can be systematically adapted through involvement of community members or stakeholders [ 30 , 33 , 35 ]. Our process differed from these mainly due to the fact that the ownership of the intervention, and thus its contextualization, resided with a different organization than the research project.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent randomized clinical trial of PFR in a sample of reunited birth parents, one parent said: Five randomized control trials, two within child welfare populations, demonstrated that Promoting First Relationships improved parent-child relationships, increased parent's knowledge of child behavior and social-emotional development, regulated child stress physiology, and improved child behavior. Importantly, PFR also reduced foster care placements by 2.5 times and supported greater stability of foster care placements once they occurred [21,[55][56][57][58]. PFR had very high retention in child protection populations and high rates of satisfaction, because it is strengths based and supports parents in their ZPD.…”
Section: Learning To Observe and Reflectmentioning
confidence: 91%
“…Implementations of the program have been shown to improve parenting outcomes, including fewer depressive symptoms, externalizing problems, and substance use, as well as child outcomes, including externalizing and internalizing behaviors [146,[241][242][243]. Other culturally-adapted home-visiting programs have been successful in improving outcomes related to CMD in Indigenous communities in the US, Canada, South Africa, and New Zea-land [244,245]. As a result of the Maternal Infant and Early Childhood Home-Visiting Program (MIECHV) authorized by the US Congress in 2010 and reauthorized in 2018, which specifically allocates money for home-visiting programs in tribal communities, Tribal MIECHV programs have been funded in 14 states [246].…”
Section: Reducing Childhood Stressorsmentioning
confidence: 99%